Analysis of the reservoirs operation in on-demand irrigation systems - Elferchichi A.; Lamaddalena N. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
Operation of a daily compensation reservoir in on-demand irrigation systems depends mainly on the geometric characteristics (depth and reservoir surface area), the downstream demand and the upstream supply. This paper presents a stochastic methodology based on real coded genetic algorithms aiming at generating the optimal supply hydrograph able to satisfy the network demand and taking into account the volume of the storage reservoir. An executable computer program was developed on C++ language. The model was applied and tested on one reservoir of the Sinistra Ofanto irrigation scheme (Italy) facing the risk of emptying during peak periods. Results demonstrated that it is possible to find solutions overcoming this risk where two theoretical alternatives were proposed based on the results of the simulations.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)